1998
DOI: 10.1016/s0014-5793(98)01435-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a retinoic acid responsive aldoketoreductase expressed in HL60 leukaemic cells

Abstract: Neutrophil and monocyte differentiation can be induced in HL60 leukaemia cells by all-trans-retinoic acid (ATRA) and 1K K,25-dihydroxyvitamin D 3 (D 3 ), respectively, whose differentiating effects can be enhanced by exposure tò anti-inflammatory agents' and steroids. We have provided evidence that this potentiation is via inhibition of the activity of an enzyme of the aldoketoreductase (AKR) family, but had failed to identify expression of known AKRs in HL60 cells. In this study, we have identified a previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…We and others have shown that the human acute myeloid leukemia cell lines HL-60 and KG1 express AKRIC3 (26,27) and that treatment of HL-60 cells with AKR1C3 inhibitors [including indomethacin (IMN)] results in increased sensitivity to the antiproliferative and prodifferentiative actions of all-trans-retinoic acid and 1␣25-dihydroxyvitamin D 3 (27,28). Similarly, exposure of HL-60 cells to an excess of PGD 2 mimics the action of AKR1C3 inhibitors in promoting all-trans-retinoic acid-induced differentiation.…”
Section: Introductionmentioning
confidence: 94%
“…We and others have shown that the human acute myeloid leukemia cell lines HL-60 and KG1 express AKRIC3 (26,27) and that treatment of HL-60 cells with AKR1C3 inhibitors [including indomethacin (IMN)] results in increased sensitivity to the antiproliferative and prodifferentiative actions of all-trans-retinoic acid and 1␣25-dihydroxyvitamin D 3 (27,28). Similarly, exposure of HL-60 cells to an excess of PGD 2 mimics the action of AKR1C3 inhibitors in promoting all-trans-retinoic acid-induced differentiation.…”
Section: Introductionmentioning
confidence: 94%
“…In several reports on the regulation of members of the aldoketo reductase superfamily, the expression of human prostaglandin F synthase (AKR 1 C3) in peripheral blood lymphocytes and HAKR e (AKR1C3) in the human myeloid leukemia-derived cell line HL60 are downregulated by con A [25] and upregulated by all-trans-retinoic acid [26], respectively. In a more recent report, a novel family member of aldoketo reductase genes in myeloid cells whose expression is regulated by IL-3 was cloned [27].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, DHRS3 (SDR16C1), described as a retinaldehyde reductase [38], was induced by RA and has a highly conserved protein sequence in mammals, suggesting a role in the control of RA synthesis [39][40][41]. AKR1C3 was up-regulated by RA treatment in HL60 cells [42], while rat AKR1B7, an enzyme with retinaldehyde reductase activity [2], was also induced by RA in the liver of vitamin A-deficient rats but not in animals fed with a vitamin-sufficient diet [39]. In contrast, human ALDH1A1 was down-regulated by RA [43], which is also consistent with the feed-back control of the RA biosynthesis.…”
Section: Role Of Cytosolic Akrs In Subcellular Retinaldehyde Metabolismmentioning
confidence: 99%